In Praise of Asclepius Aelius Aristides, Selected Prose Hymns - Russell, Donald A.; Trapp, Michael; Nesselrath, Karl-Heinz (SAPERE, 2016)
In the second century AD Aelius Aristides wrote eight prose hymns to Greek gods. This volume presents a new edition of the Greek text of four of these hymns (focusing on Asclepius), a new English translation with notes, and a number of essays shedding additional light on these texts from various perspectives.